2018
DOI: 10.1515/ntrev-2018-0080
|View full text |Cite
|
Sign up to set email alerts
|

A review on determining the refractive index function, thermal accommodation coefficient and evaporation temperature of light-absorbing nanoparticles suspended in the gas phase using the laser-induced incandescence

Abstract: In this review, the possibility of using pulsed, nanosecond laser heating of nanoparticles (NPs) is demonstrated, in order to investigate their thermo-physical properties. This approach is possible because the laser heating produces high NP temperatures that facilitate the observation of their thermal radiation (incandescence). This incandescence depends on the thermo-physical properties of the NPs, such as heat capacity, density, particle size, volume fraction and the refractive index of the particle material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 137 publications
0
1
0
1
Order By: Relevance
“…Таким образом, лазерно-индуцированная инкандесценция (ЛИИ) является перспективным методом для исследования теплофизических свойств наночастиц. Известные к настоящему времени измерения температуры сублимации сажевых частиц, измеренные при помощи метода ЛИИ, представлены в обзоре [19]. Исследования углеродных наночастиц, синтезированных при пиролизе углеводородов в ударной трубе [13,17], показали, что температура сублимации увеличивается от 2700 до 3300 K при увеличении размеров частиц от 2 до 12 nm.…”
Section: Introductionunclassified
“…Таким образом, лазерно-индуцированная инкандесценция (ЛИИ) является перспективным методом для исследования теплофизических свойств наночастиц. Известные к настоящему времени измерения температуры сублимации сажевых частиц, измеренные при помощи метода ЛИИ, представлены в обзоре [19]. Исследования углеродных наночастиц, синтезированных при пиролизе углеводородов в ударной трубе [13,17], показали, что температура сублимации увеличивается от 2700 до 3300 K при увеличении размеров частиц от 2 до 12 nm.…”
Section: Introductionunclassified
“…Thus, laserinduced incandescence (LII) is a promising technique for the study of thermophysical properties of nanoparticles. The sublimation temperatures of soot particles measured to date using the LII method were reviewed in [19]. The studies of carbon nanoparticles synthesized in the process of pyrolysis of hydrocarbons in a shock tube [13,17] revealed that the sublimation temperature increases from 2700 to 3300 K as particles grow in size from 2 to 12 nm.…”
Section: Introductionmentioning
confidence: 99%